THE SYSTEM Ag-Au-Se: PHASE RELATIONS BELOW 405 K AND DETERMINATION OF STANDARD THERMODYNAMIC PROPERTIES OF SELENIDES BY SOLID-STATE GALVANIC CELL TECHNIQUE - Osadchii E.G.; Echmaeva E.A. (My University, 2007)
The existence of the only ternary compound, Ag3AuSe2 (fischesserite), in the Ag-Au-Se system was confirmed by solid-state annealing method. The selenium analog of petrovskaite (AgAuS) was not observed under the experimental conditions (in the temperature range of 350-773 K and own vapor pressure). The solid-state reactions 2Ag(cr) + Se(s) = Ag2Se(cr) Ag(cr) + Ag3AuSe2(cr) = 2Ag(2)Se(cr) + Au(cr) 3Ag(cr) + 2AuSe(s) = Ag3AuSe2(cr) + Au(cr) were studied by the electromotive force (EMF) technique in all solid-state galvanic cells with Ag4RbI5 as a solid electrolyte. The experiments were run in a dry argon gas flow at atmospheric pressure. The following standard thermodynamic properties of the stable phases were determined at 298.15 K and 1 bar (10(5) Pa): Delta(f)G degrees(Ag2Se, low naumannite) = -49470 (+/- 130) J/mol, S degrees(Ag2Se, low naumannite) = 149.99 (+/- 0.56) J/(K center dot mol); Delta(f)G degrees(Ag2Se, high naumannite) = -47430 (+/- 290) J/mol, S degrees(Ag2Se, high naumannite) = 169.01 (+/- 0.78) J/(K center dot mol); Delta(f)G degrees(Ag3AuSe2, fischesserite) = -86450 (+/- 320) J/mol, S degrees(Ag3AuSe2, fischesserite) = 290.80 (+/- 1.26) J/(K center dot mol); Delta(f)G degrees(beta-AuSe) = -4110 (+/- 1300) J/mol; S degrees(beta-AuSe) = 75.49 (+/- 3.55) J/(K center dot mol). The phase transition point for low naumannite-high naumannite was determined at T-trs = 405.4 K, with the enthalpy of transition of Delta H-trs = -7713 (+/- 550) J/mol.
Keywords: AuSe; EMF-METHOD; FISCHESSERITE; NAUMANNITE; SOLID-STATE GALVANIC CELL; THERMODYNAMIC DATA